Poe, Fuller, and the mesmeric arts transition states in the American Renaissance - Mills, Bruce, 1958-; ebrary, Inc. (Columbia : University of Missouri Press, 2005)
"Examines how the writings of Edgar Allan Poe and Margaret Fuller draw from representations of and theories concerning animal magnetism, somnambulism, or hypnosis rendered in newspapers, literary and medical journals, pamphlets, and books, and also includes discussion of Ralph Waldo Emerson, Lydia Maria Child, and Walt Whitman"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Poe, Edgar Allan, -- 1809-1849 -- Knowledge -- Psychology; Fuller, Margaret, -- 1810-1850 -- Knowledge -- Psychology; Mesmer, Franz Anton, -- 1734-1815 -- Influence; American literature -- 19th century -- History and criticism; Mesmerism in literature; Mesmerism -- United States -- History -- 19th century; Altered states of consciousness in literature; Animal magnetism in literature; Sleepwalking in literature; Hypnotism in literature; Electronic books